Pendampingan Pembuatan Merek Kolektif One Village One Brand untuk Pengembangan IKM Kerupuk Tangkil - Dwisvimiar, Inge; Gunawati, Anne; Efriyanto, Efriyanto (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2024)
Intellectual property has an important role in supporting Micro, Small, and Medium Enterprises (MSMEs). Small and Medium Industry Entrepreneurs in Cipete Village, Curug District, Serang City produce Kerupuk Tangkil (Krutang) from melinjo fruit, but they do not yet have an official brand. The Community Partnership Program activities carried out aim to provide assistance in making collective trademark through One Village One Brand (OVOB) for local food small and medium industry in Serang City, especially Krutang small and medium industry. This program was conducted through three stages: preparation, implementation, and evaluation. The preparation stage involved visits to Cipete Village and small and medium industry of Krutang. The implementation stage included socialization on collective trademark and One Village One Brand program. The evaluation stage focused on collective trademark registration and its utilization for business development. The result of the program is the association with the collective trademark name and logo that has been agreed upon. The results show that collective trademark registration is very important to protect products and increase competitiveness. The service contributes significantly to the development of small and medium industry by providing practical guidance to utilize intellectual property.